The Art of (Un)Accompaniment: Salvadoran Child Refugee Narratives in the Twenty-first Century - Ana Patricia Rodríguez (Studies in 20th & 21st Century Literature, 2025)
In the US cultural imaginary, Salvadorans and other Central Americans are often identified as guerrillas, criminals, and “illegal” immigrants (Padilla 2022; Rodríguez 2001), but rarely are they recognized as political refugees. In particular, Salvadorans, fleeing from what a former US president indecorously called “sh*t hole countries,” have come to represent an eminent “Latino threat” (Chávez 2008). In line with this representational regime, more recent Salvadoran asylum seekers, among others, have been subject to extreme US immigration deterrent policies, such as the Zero Tolerance Policy; Remain in Mexico Plan or Migrant Protection Protocols; Public Charge Rule; and challenges to the 1997 Flores Agreement, the DACA Program, and Temporary Protected Status (TPS). This essay argues that while Salvadorans were generally denied political asylum and refugee status in the 1980s, in the twenty-first century, they are redefining the subjective space of refugees by telling their own stories in a new array of ever-expanding “refugee” narratives. Drawing from the philosophy and practice of accompaniment as proposed by slain Salvadoran archbishop and now Saint Óscar A. Romero, this essay further contends that these Salvadoran refugee texts not only document the perilous migrant journey through multiple countries, but also position readers as witnesses to the plight endured by migrants. In this process, these texts produce counternarratives, or what might be called an “art of (un)accompaniment,” invoking the words of Pope Francis (2013), which seeks to walk with migrants (refugees) and evoke compassion and legal measures for them, but often comes short of it. Focusing on the representation and focalization of Salvadoran child migrants and refugees, this essay provides a deep analysis of the poetic voices in the works of Jorge Argueta (Jimena Pérez Can Fly 2019; Caravan to the North: Misael’s Long Walk 2019) and Javier Zamora (Unaccompanied 2017).
Keywords: Salvadorans; Refugees; Asylum; Violence; Migration